Nisin and its application in oral diseases - Ka Teng Chan; Xin Song; Leyao Shen; Nian Liu; Xuedong Zhou; Lei Cheng; Jing Chen (Journal of Functional Foods, 2023)
Nisin, is a class of low molecular weight polypeptides or proteins, produced by most lactic acid bacteria, Nisin A was first identified in milk cultures in 1928 and is the only bacteriocin approved by the FDA as a food biopreservative and has been extensively studied. The antimicrobial is not limited to food-derived microorganisms, but also includes bacteria, fungi and treponemes associated with human disease. The oral cavity harbors >1000 microorganisms, where homeostasis is maintained through dynamic host-microbe interactions. With the safety of nisin in food approved for >60 years, scientists and dentists are beginning to focus on its potential application in oral health maintenance and disease control. In fact, nisin, nisin-containing dental materials, and nisin-producing probiotics show promising performance against dental caries, endodontic and periodontal diseases, and even oral cancer. In this review, we will discuss nisin, its current use, and future directions for improving oral health.